2018
DOI: 10.1016/j.freeradbiomed.2018.10.282
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of novel derivatives of vitamin D3 and lumisterol against UVB-induced damage in human keratinocytes involve activation of Nrf2 and P53 defense mechanisms

Abstract: We tested whether novel CYP11A1-derived vitamin D 3-and lumisterol-hydroxyderivatives, including 1,25(OH) 2 D 3 , 20(OH)D 3 , 1,20(OH) 2 D 3 , 20,23(OH) 2 D 3 , 1,20,23(OH) 3 D 3 , lumisterol, 20(OH)L 3 , 22(OH)L 3 , 20,22(OH) 2 L 3 , and 24(OH)L 3 , can protect against UVB-induced damage in human epidermal keratinocytes. Cells were treated with above compounds for 24 h, then subjected to UVB irradiation at UVB doses of 25, 50, 75, or 200 mJ/cm 2 , and then examined for oxidant formation, proliferation, DNA da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 60 publications
1
50
0
1
Order By: Relevance
“…In human keratinocytes, the expression of VDR is important for efficient NER, as it promotes the dissociation of XPC from DNA damage sites to allow subsequent enzymes to resume the repair of DNA photoproducts (Wong & Oh, 2021). Recently, it was reported that D3 has potent antioxidant effects on UV‐irradiated keratinocytes by activating Nrf2 (Chaiprasongsuk et al., 2019). Additionally, D3 results in increased p53 levels and its transactivation in keratinocytes and melanocytes irradiated with UV (Chaiprasongsuk et al., 2019; Dixon et al., 2005).…”
Section: Paracrine Regulation Of Melanocytes By Keratinocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In human keratinocytes, the expression of VDR is important for efficient NER, as it promotes the dissociation of XPC from DNA damage sites to allow subsequent enzymes to resume the repair of DNA photoproducts (Wong & Oh, 2021). Recently, it was reported that D3 has potent antioxidant effects on UV‐irradiated keratinocytes by activating Nrf2 (Chaiprasongsuk et al., 2019). Additionally, D3 results in increased p53 levels and its transactivation in keratinocytes and melanocytes irradiated with UV (Chaiprasongsuk et al., 2019; Dixon et al., 2005).…”
Section: Paracrine Regulation Of Melanocytes By Keratinocytesmentioning
confidence: 99%
“…Recently, it was reported that D3 has potent antioxidant effects on UV‐irradiated keratinocytes by activating Nrf2 (Chaiprasongsuk et al., 2019). Additionally, D3 results in increased p53 levels and its transactivation in keratinocytes and melanocytes irradiated with UV (Chaiprasongsuk et al., 2019; Dixon et al., 2005). The antioxidant effect of D3 is supported by the findings that its analog tacalcitol reduces hydrogen peroxide‐induced ROS and oxidative damage in melanocytes (Li et al., 2011), and enhances transactivation of Nrf2 in hydrogen peroxide‐induced melanocytes (Tang et al., 2018).…”
Section: Paracrine Regulation Of Melanocytes By Keratinocytesmentioning
confidence: 99%
“…Second, this study is limited by the lack of information on the natural compounds that exert photoprotective effect. Plant extracts, natural compounds, or metabolites such as melatonin [ 33 ] and vitamin D compounds [ 34 ] have been considered as one of the most promising sources to prevent or ameliorate the effects of UVB. Some yin-tonic herbal medicines possess antioxidant properties, having rich antioxidants such as phenolic compounds, which contribute to the yin-tonic or antioxidative activity [ 35 , 36 ] as well as anti-inflammatory properties [ 35 ], implying that yin-yang theory is somewhat equivalent to the modern theory of antioxidant-oxidant balance.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-aging strategies target diverse mechanisms involved in skin aging, such as oxidative stress, mitochondrial dysfunction, cellular senescence, and epigenetic changes [1,[31][32][33][34]. For example, melatonin and its metabolites, non-calcemic secosteroids, lumisterol derivatives, polyphenols, and vitamins represent promising anti-aging agents [1,35,36]. It has also been reported that natural products, such as epigallocatechin-3-gallate, genistein, curcumin, and resveratrol, can affect the activity of various epigenetic regulating enzymes, such as DNA methyltransferase, HATs, and HDACs [37,38].…”
Section: Discussionmentioning
confidence: 99%